Pengaruh Promosi Word Of Mouth, Brand Image, Influencer Marketing, Terhadap Minat Beli Skincare Pada Produk Kecantikan Drw Skincare - Nurul Jannah; Eko Agus Alfianto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study was conducted to determine the Effect of Word Of Mouth Promotion, Brand Image, Influencer Marketing, On Skincare Buying Interest In Drw Skincare Beauty Products. This type of research uses descriptive research with a quantitative approach, with the distribution of questionnaires as a data collection technique. The sampling method uses purposive sampling techniques, which is a sampling technique where people are selected as samples in accordance with the purpose of the study, the sample used as many as 100 respondents through the distribution of questionnaires. The data analysis method used in this study is multiple linear regression with calculation analysis using SPSS 23. The results of this study show that: 1. Word of mouth variables have a positive and significant effect on Skincare Buying Interest in Drw Skincare Beauty Products, 2. Brand image variables have a positive and significant effect on Skincare Buying Interest in Drw Skincare Beauty Products, 3. Influencer marketing variables have a positive and significant effect on Skincare Buying Interest in Drw Skincare Beauty Products. Hypothesis tests include T tests and F tests, obtained Fcalculate > F tables so that the resulting regression model is appropriate and can be used to predict the results of influence. The results of the T test for the variables word of mouth, brand image, influencer marketing were obtained by (WOM) Thitung (2,479) > from Ttabel (1,985), (BI) from Thitung (17,307) > from Ttabel (1,985), (IM) from Thitung (10,722) > from Ttabel (1,985) It can be concluded that the variables of word of mouth, brand image, influencer marketing have an influence and are significant on Skincare Buying Interest in Drw Skincare Beauty Products